Tryptophan-tagged peptide from serine threonine-protein kinase of Channa striatus improves antioxidant defence in L6 myotubes and attenuates caspase 3-dependent apoptotic response in zebrafish larvae - Issac, Praveen Kumar; Lite, Christy; Guru, Ajay; Velayutham, Manikandan; Kuppusamy, Giva; Saraswathi, N. T.; Al Olayan, Ebtesam M.; Aloufi, Abeer S.; Elokaby, Mohamed A.; Elumalai, Preetham; Arshad, Aziz; Arockiaraj, Jesu (Springer, 2021)
This study reports the antioxidant property and molecular mechanism of a tryptophan-tagged peptide derived from a teleost fish Channa striatus of serine threonine-protein kinase (STPK). The peptide was tagged with tryptophan to enhance the antioxidant property of STPK and named as IW13. The antioxidant activity of IW13 peptide was investigated using in vitro methods such as DPPH, ABTS, superoxide anion radical scavenging and hydrogen peroxide scavenging assay. Furthermore, to investigate the toxicity and dose response of IW13 peptide on antioxidant defence in vitro, L6 myotubes were induced with generic oxidative stress due to exposure of hydrogen peroxide (H2O2). IW13 peptide exposure was found to be non-cytotoxic to L6 cells in the tested concentration (10, 20, 30, 40 and 50 μM). Also, the pre-treatment of IW13 peptide decreased the lipid peroxidation level and increased glutathione enzyme activity. IW13 peptide treatment upregulated the antioxidant enzyme genes: GPx (glutathione peroxidase), GST (glutathione S transferase) and GCS (glutamine cysteine synthase), in vitro in L6 myotubes and in vivo in zebrafish larvae against the H2O2-induced oxidative stress. The results demonstrated that IW13 renders protection against the H2O2-induced oxidative stress through a cellular antioxidant defence mechanism by upregulating the gene expression, thus enhancing the antioxidant activity in the cellular or organismal level. The findings exhibited that the tryptophan-tagged IW13 peptide from STPK of C. striatus could be a promising candidate for the treatment of oxidative stress–associated diseases.